Perdagangan Internasional Indonesia: Sebuah Komparasi di Masa Pandemi COVID-19 - Maria Agape Widya Prasetya; Christien Simorangkir; Dina Margaretha Ajik Pribadi (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2022)
COVID-19 pandemic that has attacked almost all countries in the world since the end of 2019 until now certainly has an impact on international trade. This impact is certainly also felt by Indonesia as a open market operation country. Purpose of this study is to see whether the COVID-19 pandemic affects international trade, both export and import activities with oil and gas and non-oil and gas types. The data used is the total value of exports and imports, oil and gas, and non-oil and gas from 2019.8 to 2020.9 or nineteen months before the COVID-19 pandemic and nineteen months during the COVID-19 pandemic obtained from the Monthly Trade report published by the Ministry of Trade of the Republic of Indonesia. This study uses data analysis techniques, namely Paired Sample T Test and Mann-Whitney U Test. The results showed that there was no difference in the value of nonoil and gas imports before and during the COVID-19 pandemic, while total exports, oil and gas exports, non-oil exports, total imports, and imports of oil and gas experienced significant changes or differences in value in the period before and during the COVID-19 pandemic. The Indonesian economy during this crisis turned out to be stronger on the import side because the value of non-oil and gas imports didn’t show a significant difference both before and during the COVID-19 pandemic.